Immune Dysfunction and Autoimmunity as Pathological Mechanisms in Autism Spectrum Disorders - Hughes, Heather K.; Mills Ko, Emily; Rose, Destanie; Ashwood, Paul (Frontiers in Cellular Neuroscience, 2018)
Autism spectrum disorders (ASD) are a group of heterogeneous neurological disorders that include autism, Asperger syndrome, and pervasive developmental disorder not otherwise specified. These highly variable disorders are clinically characterized by deficits in social interactions, communication, and stereotypical behaviors. Incidences have risen from 1 in 10,000 in 1972 to 1 in 59 in 2014 and while causative connections have not been proven in the majority of cases, many current studies focus on the combined effects of genetics and environment. Strikingly, a distinct picture of immune dysfunction has emerged and been supported by many independent studies over the past decade. Many players in the immune-ASD puzzle may be mechanistically contributing to pathogenesis of these disorders, including skewed cytokine responses, differences in total numbers and frequencies of immune cells and their subsets, neuroinflammation, and adaptive and innate immune dysfunction, as well as altered levels of immunoglobulin and the presence of autoantibodies which have been found in a substantial number of individuals with ASD. This review summarizes the latest research linking ASD, autoimmunity and immune dysfunction, and discusses evidence of a potential autoimmune component of ASD.